A Study of Individual, Group and Organizational Mechanism: A Case of AEON Hypermarket in Malaysia - Mursyidatunnajwa Mursyidatunnajwa; Daisy Mui Hung Kee; Liyana Hamizah; Haruki Matsushita; Kureha Suzuki; Ruchika Singh; Nitish Jauhari (Journal of The Community Development in Asia, 2020)
This study aims to examine the relationship between individual, group and organizational mechanism in Aeon, the biggest hypermarket in Malaysia. Aeon’s parent company and headquarter is in Japan. The paper focuses on Aeon Hypermarket Malaysia. Aeon started its operations in Malaysia since September 1984. The paper presents how Aeon successfully attracts their customers and succeed in their business in Malaysia. The paper also discusses the marketing strategies employed by Aeon such as new product mixing methods, pricing strategies and promotion mix and how Aeon uses the marketing strategies to increase their profits and successfully positions themselves as the leading hypermarket in Malaysia. The study employs qualitative methodology using interviews. The managers were interviewed to obtain rich information to answer the objectives of the study. The paper concludes with some recommendation.